Aloe barbadensis miller versus silver sulfadiazine creams for wound healing by secondary intention in dogs and cats: A randomized controlled study. (April 2018) - Drudi, Dario; Tinto, Debora; Ferranti, Davide; Fiorelli, Federico; Pozzo, Mara Dal; Capitani, Ombretta
Abstract: The objective of this study was to compare the effectiveness of the topical application of Aloe barbadensis Miller (juice and fresh gel) to skin wounds, in dogs and cats, with that of topically applied silver sulfadiazine cream. The sample included 16 patients with cutaneous wounds (13 dogs and three cats) that were divided into three groups. Aloe vera "juice" and "fresh gel" were applied for groups I and II, respectively, while silver sulfadiazine was applied for the control group III. In order to evaluate the healing of wounds, the following parameters were taken into consideration: the percentage of wound shrinkage, the healing time and the macroscopic appearance of the scarring process. The interpretation of the data relating to the percentage of wound shrinkage showed a faster rate for groups I and II compared to that of group III. However, the wound shrinkage rates between "juice" and "fresh gel" protocols were not significantly different. Aloe vera was more effective than silver sulfadiazine, in accelerating wound shrinkage, reducing healing time and decreasing the severity of the associated injuries. Highlights: Topical application of Aloe barbadensis Miller (juice and fresh gel) to skin wounds. The percentage of wound shrinkage, the healing time and the macroscopic appearance of the scarring process were evaluated. Aloe vera seems to accelerate wound shrinkage and reduce healing time.